MODEL IMPLEMENTASI KOLABORASI SEKOLAH MENENGAH KEJURUAN NEGERI 1 BENGKULU SELATAN DALAM PENINGKATKAN KOMPETENSI LULUSAN - Dani, Rahiman; Defrianto, Novon; Alexsander, Alexsander (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
Collaboration Implementation Model of State Vocational High School 1 Bengkulu Selatan is very important in Improving Graduate Competence. State Vocational High School 1 Bengkulu Selatan is one of the Vocational Schools with the status of a Center of Excellence in South Bengkulu Regency. This study aims to analyze the implementation model and the collaborative activities carried out by State Vocational High School 1 Bengkulu Selatan in collaboration with the Industrial World and the Manna Region III Education Office Branch. This study uses a qualitative approach method with data collection techniques through interviews, observations, and documentation studies. The informants of this study consisted of educational institutions, the government, and the industrial world. The results of this study indicate that the implementation of collaboration has been running in accordance with the technical instructions and techniques determined by the Director General of Vocational Education. It's just that this collaboration has not been fully implemented in all existing department competencies. This collaboration model can be seen in its full implementation in the Visual Communication Design (DKV) department, so that it can be a guideline for other schools and departments in improving Graduate Competencies.